A MODEL-BASED APPROACH FOR DESCRIBING OFFLINE NAVIGATION OF WEB APPLICATIONS - FELIX ALBERTOS-MARCO; VICTOR M.R. PENICHET; JOSE A. GALLUD; MARCO WINCKLER (Journal of Web Engineering, 2016)
The ubiquitousness of the Internet is changing the way users perform their tasks. There is a trend and sometimes a real need to be always connected. The client-server paradigm used in the Web greatly facilitates the consumption of contents. However, there are many situations where the user’s tasks in a Web application might be interrupted due to an unexpected loss of connectivity, temporary unavailability of Web servers, external events, etc., setting the browse to an offline state. The availability of local storage in Web browsers might suggest that users can perform some of their tasks when offline. Nonetheless, several technical constraints might prevent users from efficiently resuming their tasks over the Web after the offline period. In this paper we present a model-based approach called the Offline Model, which is aimed at supporting the execution of tasks interrupted by loss of connectivity based on user navigation with Web applications. Furthermore, we demonstrate how the Offline Model can be exploited to mitigate some of the disruptive effects of interruptions, due to offline navigation, on user tasks based on Web navigation in existent Web applications. The feasibility of such a model approach is demonstrated by a support tool and illustrated by a case study of navigation in a real scenario: the DBLP Web site.